A Review of the Health Implications of Heavy Metals in Food Chain in Nigeria - Nkwunonwo, Ugonna C. (ScientificWorldJournal, 2020)
Heavy metals such as Zn, Pb, Fe, and Cu are abundant in the environment and contribute largely to the sustainability and equilibrium of ecosystem processes. However, because of their bioaccumulation, nondegradability, and the excessive amounts in which they exist, these metals contaminate the food chain and subsequently become a source of toxicity to human beings and the entire ecological function. This is a major issue of concern within the study of environmental science and geochemistry. Although there is a global significance to the issue, it seems more immediate for the developing countries (DCs) such as Nigeria, where the pressure of the teeming population escalates the exigency for human sustainability, food security, and total eradication of hunger. Within the Nigerian context, many studies have examined this all-important issue, but most of these studies are fragmented and limited within the purview of mostly individual states and localities within the country. Taken on a wider geographical scale, the discussions and perspectives of these studies on heavy metal contamination of the food chain offer insufficient insight and expose merely a snapshot of the actual situation. As a result of this, a country-wide knowledge base of the implications of heavy metals on the food chain is lacking. Thus, the present study synthesises existing literature and their findings to create a knowledge base on the vulnerability of the food chain in Nigeria. Aquatic foods, fruits, vegetables, and major staple food such as tubers are the major host of carcinogenic and mutagenic components of heavy metals in Nigeria. This study motivates the Standard Organisation of Nigeria (SON), along with other food and agricultural agencies, to intensify their efforts in monitoring and analysing food components, and we advise consumers to eat with certain degrees of caveat.